The Effectiveness of Using Smartphone-Based Phyphox in Field Practice Tilt to Improve Students' Creative Thinking Skills - Rusdin, Muhammad Epi; Prasetyo, Erwin; Anwar, Zaina; Pujianti Bejahida Donuata; Nurfadilah; Farizi, Zakaria Al (Jurnal Penelitian Pembelajaran Fisika, 2025)
The use of technology is a solution to overcome problems in physics learning. This study aims to determine the effectiveness of using Smartphone-based Phyphox in improving students' creative thinking skills. The design used in this research is a nonequivalent pre-test and post-test control group design. This study used a purposive sampling technique to get two groups. The statistical analysis used was independent sample t-test. The results of the analysis showed that there was an effect of using Smartphone-based Phyphox in improving students' creative thinking skills, so it was effective in the learning process. In general, this research can contribute to the field of education, especially physics learning, to optimize the use of technology as a learning medium. This learning strategy allows students to participate directly in proving the concept of the material. In addition, this model can be an alternative to active learning in improving students' creative thinking.